Produktivitas dan Pendapatan Petani Jagung Kuning Hibrida di Desa Marobea Kecamatan Saweriga di Kabupaten Muna Barat - Fitriyani Fitriyani; Ine Fausayana; Samsul Alam Fyka (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to determine: (1) To determine the productivity of hybrid yellow corn farmers in Mrobea Village, Sawerigadi District, West Muna Regency and (2) To determine how much income hybrid yellow corn farmers get in Marobea Village, Sawerigadi District, West Muna Regency. The results of this study indicate that (1) The productivity of hybrid yellow corn farmers in Marobea Village, Sawerigadi District, West Muna Regency is 2,127/kg, which can be said to be quite productive with an average production of 3.128/kg and an average land area of ​​1.47/ha. (2) The amount of income is obtained from the difference between total income of Rp14,050,976/ha/planting season with total production costs of Rp4,365,666/ha/planting season, resulting in an income of an average of Rp9,685,310/ha/planting season.